Detection of Alzheimer Disease Using Machine Learning - Deepak Patel*, Geraldine Bessie Amali D (International Journal of Advanced Science and Technology, 2020)
Alzheimer disease affects brain functioning. This is the major case of 'dementia' disease. This disease is slowly destroying our memory and thinking capability. This disease is one of most pervasive types of Dementia that influencing old age people. It caused by a genetic lifestyle and environmental factors. We chose MRI (Magnetic Resonance Imaging) related data to investigate symptoms of the disease. Machine Learning is a contemporaneous approach that addressing detect and identify without human being’s involvement. Too identify the problem in medical image processing with the help of the Ada Boost algorithm, Gradient Boost algorithm, and Random Forest Algorithm. We get a better type of detection of subject problems. In the dataset, we take a longitudinal dataset from the (OASIS) , it provides real time data for medical. It is a collection of 373 subject of MRI data. The result provides better performance for dementia. The used method is shown to achieve accuracy is get 91%.